Conocimiento sobre el desarrollo del lenguaje oral en padres de familia de niños del nivel inicial 3 años de instituciones educativas de gestión pública y privada - Salinas Rodríguez, Graciela Patricia (2023)
Considering that the family environment is the main means for children's language acquisition, this research aims to compare the knowledge about the development of oral language in parents of children from the Initial Level 3 years of Educational Institutions of public and private management. The population and sample were made up of 35 families from two educational centers, one publicly managed and the other privately managed. The first, with 20 families, corresponding to the district of La Victoria and the second, with 15 families belonging to the district of San Borja. The instrument applied was a Questionnaire previously prepared by the researchers based on the four components of language development with simple questions of dichotomous selection, which passed through the criteria of expert judges. The results indicate that there is a significant difference in the knowledge about the development of oral language in parents of children of the Initial Level 3 years, according to the type of educational management, where levels medium and low were found respectively. Likewise, a significant difference was evidencedin the knowledge about the development of oral language in its different components such as lexicology- semantics, morphology-syntax and phonological phonetic.